PENINGKATAN PEMAHAMAN PENCEGAHAN DAN HUKUM KESEHATAN TERKAIT PANDEMI COVID-19 DI KLINIK CAHAYA KEMANG, KABUPATEN BOGOR - Ratna Puspita; Isniani Ramadhani Sekar Prabarini; Erna Harfiani; Putra Sang Fajar El Harry (Dharma Pengabdian Perguruan Tinggi (DEPATI), 2022)
The spread of Covid-19 in Indonesia is still very high. One area that has a high impact is Kemang District, which is located in Bogor Regency. The Kemang District people need the right information to help maintain their health and prevent the transmission of Covid-19. Educational activities regarding Covid-19 aim to motivate the public so that they support the government's movement in breaking the chain of spread of Covid-19. The team provided educational media in the form of posters, pocket books, and videos on prevention of transmission and health laws related to Covid-19. In addition, the provision of materials online using ZOOM. The public understands that the prevention of Covid-19 transmission can be done with health protocols and increasing body resistance with a healthy lifestyle and vaccination. A healthy lifestyle includes maintaining a balanced diet with nutrition, exercise, and sleep patterns. Traditional medicines and supplements that are often consumed by the community also need to be adjusted to the needs of each individual. The public also gains insight into health laws related to Covid-19.